2019
DOI: 10.1088/1757-899x/546/4/042047
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Methyl Orange Photodegradation Using TiO2-Zeolite Photocatalyst and H2O2 in Acid Condition

Abstract: This paper discusses an optimisation of methyl orange photodegradation using TiO2-zeolite photocatalyst and H2O2 (with condition of pH 2, 10 ppm, UV light). A 15 mmol TiO2 in 1 gram activated zeolite was used. The influence of H2O2 concentration (4, 8, 12, 16%) and irradiation time (20, 30 40, 50, 60 minutes) was also investigated, as well as initial methyl orange concentration (10, 20, 30 ppm) toward reaction rate constant. As the H2O2 concentration increase, the photodegradation percentage is also increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Meanwhile, methyl orange before the catalytic process was identified at m / z 327. A signal appeared with m / z 304 and 306 from methyl orange, which lost sodium ions and underwent rearrangement [ 70 ]. The results of a mixture of dyes refer to the retention time of each component before being mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, methyl orange before the catalytic process was identified at m / z 327. A signal appeared with m / z 304 and 306 from methyl orange, which lost sodium ions and underwent rearrangement [ 70 ]. The results of a mixture of dyes refer to the retention time of each component before being mixed.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was then kept in dark to attain adsorption-desorption equilibrium. The sample was then kept under standard light with constant and continuous stirring for different irradiation times (1,3,5,7,9, and 11 min). After the reaction time completion, the photocatalyst was separated through centrifugation (12000 rpm for 10 min).…”
Section: Photodegradation Study Of Methylene Blue Dyementioning
confidence: 99%
“…This is because at the beginning formation of • OH radicals is faster and the more availability of the active site for dye adsorption. After a particular reaction time, the remaining active site is not easy to ll because of the repulsive force between the molecules on the surface with the bulk phase, and thus after sometime the %degradation tends to be constant (Aziztyana et al 2019). The sustainability of Fe 2 O 3 NPs is evaluated by utilizing recovered and re-recovered Fe 2 O 3 NPs under the same experimental conditions.…”
Section: Photodegradation Of Methylene Bluementioning
confidence: 99%
“…Due to their industrial applications, dyes are found in effluents from pharmaceutical, pulp and paper, paint, and some other industries. About one fifth of all the dyes produced worldwide gets discharged into waterbodies through the effluents from textile industries [10].The most abundant compounds (60 -70 %) in textile waste are azo dyes [11].…”
Section: Introductionmentioning
confidence: 99%